Investigative computer forensics : the practical guide for lawyers, accountants, investigators, and business - Laykin, Erik. (Hoboken : John Wiley, 2013)
"Having worked with Erik on some of the most challenging computer forensic investigations during the early years of this industry's formation as well as having competed with him earnestly in the marketplace ... I can truly say that Erik is one of the unique pioneers of computer forensic investigations. He not only can distill complex technical information into easily understandable concepts, but he always retained a long, term global perspective on the relevancy of our work and on the impact of the information revolution on the social and business structures of tomorrow."--The Foreword by James Gordon, Managing Director, Navigant Consulting, Inc.
Get the knowledge you need to make informed decisions throughout the computer forensic investigation process. Investigative Computer Forensics zeroes in on a real need felt by lawyers, jurists, accountants, administrators, senior managers, and business executives around the globe: to understand the forensic investigation landscape before having an immediate and dire need for the services of a forensic investigator. Author Erik Laykin, leader and pioneer of computer forensic investigations, presents complex technical information in easily understandable concepts ... Get the knowledge you need to make tough decisions during an internal investigation or while engaging the capabilities of a computer forensic professional with the proven guidance found in Investigative Computer Forensics.
Foreword -- Preface -- This book's setup -- Acknowledgments -- Introduction -- The glue -- A primer on computers and networks -- Computer forensic fundamentals -- Investigative fundamentals -- Index.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Computer crimes -- Investigation; Computer security; Fraud investigation; Corporations -- Corrupt practices; Computer crimes -- Investigation; Computer security; Fraud investigation; Corporations -- Corrupt practices; LAW -- Forensic Science; Computer crimes -- Investigation; Computer security; Corporations -- Corrupt practices; Fraud investigation; Computer crimes / Investigation; Computer security; Fraud investigation; Corporations / Corrupt practices; Electronic books